Tombstoneite, a new mineral from Tombstone, Arizona, USA, with a pinwheel-like Te6+O3(Te4+O3)3 cluster. (18th February 2023) - Kampf, Anthony R.; Mills, Stuart J.; Housley, Robert M.; Ma, Chi; Thorne, Brent
Abstract: The new mineral tombstoneite (IMA2021-053), (Ca0.5 Pb0.5 )Pb3 Cu 2+ 6 Te 6+ 2 O6 (Te 4+ O3 )6 (Se 4+ O3 )2 (SO4 )2 ⋅3H2 O, occurs at the Grand Central mine in the Tombstone district, Cochise County, Arizona, USA, in cavities in quartz matrix in association with jarosite and rodalquilarite. Tombstoneite crystals are green pseudohexagonal tablets, up to 100 μm across and 20 μm thick. The mineral has a pale green streak and adamantine lustre. It is brittle with irregular fracture and a Mohs hardness of 2½. It has one perfect cleavage on 001. The calculated density is 5.680 g cm –3 . Optically, the mineral is uniaxial (–) and exhibits pleochroism: O = green, E = light yellow green; O > E . The Raman spectrum exhibits bands consistent with Te 6+ O6, Te 4+ O3, Se 4+ O3 and SO4 . Electron microprobe analysis provided the empirical formula (Ca0.51 Pb0.49 )Σ1.00 Pb3.00 Cu 2+ 5.85 Te 6+ 2.00 O6 (Te 4+ 1.00 O3 )6 (Se 4+ 0.69 Te 4+ 0.24 S0.07 O3 )2 (S1.00 O4 )2 ⋅3H2 O. Tombstoneite is trigonal, P 321, a = 9.1377(9), c = 12.2797(9) Å, V = 887.96(18) Å 3 and Z = 1. The structure of tombstoneite ( R 1 = 0.0432 for 1205 I > 2σ I ) contains thick heteropolyhedral layers comprising Te 6+ O6 octahedra, Jahn-Teller distorted Cu 2+ O5 pyramids, Te 4+ O3 pyramids and Se 4+ O3 pyramids. Pb 2+ cations without stereoactive 6s 2 lone-pair electrons are hosted in pockets in the heteropolyhedral layer. Pb 2+ cations, possibly with stereoactive 6s 2 lone-pair electrons, are located in the interlayer region along with SO4 tetrahedra and H2 O groups. Within the heteropolyhedral layer, the Te 6+ O6 octahedra and the Te 4+ O3 pyramids form finite Te 6+ O3 (Te 4+ O3 )3 clusters with a pinwheel-like configuration. This is the first known finite complex including both Te 4+ and Te 6+ polyhedra in any natural or synthetic tellurium oxysalt structure.